Planejamento estratégico e a gestão por processo: estudo de caso em uma Indústria de Plástico - Brovoski, Ana Paula dos Santos (2020)
The present research had as objective to elaborate the strategic planning and to map the processes of the Alfa industry. The methodological procedure used for its development was applied and descriptive research, of qualitative nature. The research was developed through action research. To conduct the study, meetings were held with managers, the construction of SWOT and CANVAS analysis, as well as the creation of strategic planning and process mapping. For the latter, interviews were conducted with employees and the Bizagi Software was used. Through the analysis of the results extracted from the business diagnosis, it was possible to carry out, in addition to the mapping of the main organizational activities and strategic planning, intervention suggestions divided into four proposals and composed of actions, among them the application of the organizational climate survey, the survey of costs of the services currently provided, the formation of partnerships and the study of the expansion of the Alfa industry. This implies a new way for managers to understand the organizational functioning and the purpose of the business, changing the way they operate and adding management by process to the organizational day-to-day.